ANGPTL3 overcomes sorafenib resistance via suppression of SNAI1 and CPT1A in liver cancer - Yang-Hsiang Lin; Cheng-Yi Chen; Hsiang-Cheng Chi; Meng-Han Wu; Ming-Wei Lai; Chau-Ting Yeh (Translational Oncology)
Liver cancer, encompassing hepatocellular carcinoma (HCC) and hepatoblastoma, the latter of which primarily occurs in early childhood, is the most common malignant tumor arising from liver and is responsible for a significant number of cancer-related deaths worldwide. Targeted drugs have been used for anti-liver cancer treatment in the advanced stage, while their efficacy is greatly compromised by development of drug resistance. Drug resistance is a complicated process regulated by intrinsic and extrinsic signals and has been associated with poorer prognosis in cancer patients. In the current study, online available dataset analysis uncovered that angiopoietin-like protein 3 (ANGPTL3) manifested lower expression in sorafenib-resistant liver cancer cell lines. Additionally, ANGPTL3 was downregulated in HCC tissues, with its expression positively correlated with good prognosis. Functionally, ectopic expression of ANGPTL3 re-sensitized sorafenib-resistant cells, enhancing the sorafenib-induced reduction in cell viability and migration by suppressing zinc finger protein SNAI1 (SNAI1) expression and the protein stability of carnitine O-palmitoyltransferase 1, liver isoform (CPT1A). Clinical correlation analysis revealed that ANGPTL3 was negatively associated with SNAI1 expression. In conclusion, we identify a novel association between ANGPTL3, SNAI1 and CPT1A on sorafenib therapeutic response. Targeting ANGPTL3/SNAI1/CPT1A axis may serve as a therapeutic approach to improve prognosis of liver cancer patients with sorafenib resistance.